2010
DOI: 10.1016/j.str.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Arginine Finger to ATP Triggers Large Conformational Changes in NtrC1 AAA+ ATPase for Remodeling Bacterial RNA Polymerase

Abstract: SUMMARY The NtrC-like AAA+ ATPases control virulence and other important bacterial activities through delivering mechanical work to σ54-RNA polymerase to activate transcription from σ54-dependent genes. We report the first crystal structure for such an ATPase, NtrC1 of Aquifex aeolicus, in which the catalytic arginine engages the gamma-phosphate of ATP. Comparing the new structure with those previously known for apo and ADP-bound states supports a novel rigid-body displacement model that is consistent with lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 37 publications
5
89
1
Order By: Relevance
“…5). Although it was observed earlier that s54 protein can bind with other oligomeric states of the bEBPs (Rappas et al 2005;Chen et al 2010), we propose that the asymmetric hexamer provides a unique configuration for guiding the protein-protein interaction. Our preliminary EM data for the NtrC1 ATPase in complex with s54-promoter-RNAP suggest the presence of a similarly asymmetric NtrC1 hexamer (S Chowdhury, S DeCarlo, and BT Nixon, unpubl.).…”
Section: The Gap Interface Of the Ntrc1 Atpase As A Nucleotide Releasmentioning
confidence: 53%
See 2 more Smart Citations
“…5). Although it was observed earlier that s54 protein can bind with other oligomeric states of the bEBPs (Rappas et al 2005;Chen et al 2010), we propose that the asymmetric hexamer provides a unique configuration for guiding the protein-protein interaction. Our preliminary EM data for the NtrC1 ATPase in complex with s54-promoter-RNAP suggest the presence of a similarly asymmetric NtrC1 hexamer (S Chowdhury, S DeCarlo, and BT Nixon, unpubl.).…”
Section: The Gap Interface Of the Ntrc1 Atpase As A Nucleotide Releasmentioning
confidence: 53%
“…What does appear certain is that all of the multimeric ATPases need to break rotational symmetry or lower it in order to function efficiently. That requirement may explain inhibition of the ATPase activity by saturating amounts of ATP in the bEBPs PspF and NtrC1 (Schumacher et al 2008;Chen et al 2010).…”
Section: Topologically Open Hexamer As a General Trend?mentioning
confidence: 99%
See 1 more Smart Citation
“…The altered amino acid is located next to an annotated arginine finger (Arg311) and within an annotated 54 interaction domain. Binding of the arginine finger to ATP triggers a large conformational shift, which is essential for interaction with 54 -RNA polymerase (40). Thus, the mutation of Tyr310 may negatively affect the interaction with 54 -RNA polymerase, resulting in the absence of pxr transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Such methods include cryo EM and SAXS. Cryo EM has revealed flexibility in the N-domains of E. coli AAA + protein ClpA (Ishikawa et al, 2004) and SAXS experiments have shown large conformational changes in NtrC1 (Chen et al, 2010). Although in some cases conformational changes observed with different methods do not completely agree, it is widely accepted that AAA + proteins undergo dynamic movements during their catalytic cycle.…”
Section: Conformational Changes In Aaa + Proteinsmentioning
confidence: 99%